The determinants of consumers purchase intention toward counterfeit product in Malaysia - Goh Hui Ni; Marina Isa; Mohamad Zulfahmi Mohd Noor; Nada Afiqah Redzuan (2016)
The purpose of this study is to understand the consumers’ attitude towards counterfeit products. It helps the firms to understand the factors that influence consumers’ attitude and intention to buy the counterfeits. This study was carried out based on previous studies of Chaudhry (2014), Diwasaril (2013) and Wang. F. et.al (2005). An online survey questionnaire was used for self administered data collection of 386 respondents who are eighteen years old and above and reside in Malaysia. Convenient sampling and Statistical Package for Social Science (SPSS) was used for data analysis. Descriptive analysis, reliability analysis and bivariate analysis were chosen to examine the hypotheses with using Pearson correlation. The lead presenting of this research is to reveal that consumers prefer to buy counterfeit products since prices of original brands is high and product characteristics of counterfeit products. This research gives understanding to manufacturers of genuine brand about the factors that influence on consumers’ attitude and intention to buy the counterfeit products and hence helps in implementing effective marketing strategies. Besides, the result of this study helps in exposing researchers and students with relevant information. This research has proven that few factors namely value consciousness, social status, price consciousness and easy access affect consumers purchase intention towards counterfeit products. However, the scope of study is not limited to any product as the main objective of this study is to evaluate consumers’ attitude towards counterfeit products as an overall.